OPTIMASI ANALISIS DAN EFISIENSI ENERGI TERMAL MENGGUNAKAN TUNGKU SEKAM SEBAGAI BAHAN BAKAR ALTERNATIF RUMAH TANGGA (STUDI KASUS : PRAKTIKUM TERMODINAMIKA) - Zahra Syahira; Dwiky Agung Adi Nugroho; Royyan Faizin; Fajrul Kamil Ramadhan; Sejahtera Sejahtera; Salahuddin Perdana; Muhammad Ahyad; Angga Khalifah Tsauqi; Alif Musthafa Thariq; Ahmad Yani; Irzaman Irzaman (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Fuel usage in households commonly used in all levels of society. Has become a daily needs of households in the use of fuels, especially for cooking. Limited supply of fuel gas causes the transition to alternative fuels such as rice husk furnace. Rice husk furnace is a medium that uses materials rice husk and in this study applied in thermodynamics experiment in the Department of Physics, IPB semester 3. In optimizing analysis and the efficiency of thermal energy using rice husk furnace as an alternative fuel of households conducted in three treatments (1 kg , 1.5 kg and 2 kg) of water boiling on the rice husk furnace. Rice husk furnace produces average value of thermal energy efficiency of 4.64% when the boiled water for 1 kg, 4.16% for 1.5 kg in the boiled water and 6.57% when water boil for 2 kg. Based on these results when applied in the community, will greatly assist the government in the national energy endurance. Keywords: Fuel, rice husk, rice husk furnace, efficiency of thermal energy, energy endurance.